The cultural morphospace of ritual form: examining modes of religiosity cross-culturally - Atkinson, Q; Whitehouse, H (Elsevier, 2011)
Ethnographic, historical, archaeological and experimental work suggests the existence of two basic clusters of ritual dynamics or 'modes of religiosity' - a low-frequency, high-arousal cluster linked to the formation of small cohesive communities (imaginistic mode) and high-frequency, low-arousal cluster associated with larger, more centralized social morphology (doctrinal mode). Currently, however, we lack a large-scale survey of ritual variation on which to test such predictions. Here, we compile data on 645 religious rituals from 74 cultures around the globe, extracted from the Human Relations Area Files, revealing that the cultural morphospace of ritual form favours rituals that are indeed either low-frequency and highly dysphorically arouding or high-frequency with lower arousal and that these ritual dynamics are linked to group size and structure. These data also suggest that low dysphoric arousal, high-frequency rituals may have been tied to the advent of agriculture and subsequent emergence of the first large-scale civilizations.